Thienothiophene-based organic light-emitting diode: synthesis, photophysical properties and application - Isci, Recep; Ozturk, Turan (Beilstein Journal of Organic Chemistry, 2023)
A donor–π–acceptor (D–π–A)-type pull–push compound, DMB-TT-TPA (8), comprising triphenylamine as donor and dimesitylboron as acceptor linked through a thieno[3,2-b]thiophene (TT) π-conjugated linker bearing a 4-MeOPh group, was designed, synthesized, and fabricated as an emitter via a solution process for an organic light-emitting diode (OLED) application. DMB-TT-TPA (8) exhibited absorption and emission maxima of 411 and 520 nm, respectively, with a mega Stokes shift of 109 nm and fluorescence quantum yields both in the solid state (41%) and in solution (86%). The optical properties were supported by computational chemistry using density functional theory for optimized geometry and absorption. A solution-processed OLED was fabricated using low turn-on voltage, which had performances with maximum power, current, and external quantum efficiencies of 6.70 lm/W, 10.6 cd/A, and 4.61%, respectively.
Keywords: OLED; organoboron; solution processes; thienothiophene; triphenylamine